DRESS syndrome in a patient with chronic hepatic encephalopathy - Roberto Giulio Romanelli; Tommaso Gabbani; Maria Marsico; Fabrizia Natucci; Veronica Almerigogna; Elisa Triboli; Sergio Generini; Cristina Stasi; Giacomo Laffi (Turkish Journal of Gastroenterology, 2019)
-